Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/2191-219x-3-69
|View full text |Cite
|
Sign up to set email alerts
|

Measuring dopaminergic function in the 6-OHDA-lesioned rat: a comparison of PET and microdialysis

Abstract: Background[18 F]fluorodopa (FDOPA) positron emission tomography (PET) allows assessment of levodopa (LDOPA) metabolism and is widely used to study Parkinson's disease. We examined how [18 F]FDOPA PET-derived kinetic parameters relate the dopamine (DA) and DA metabolite content of extracellular fluid measured by microdialysis to aid in the interpretation of data from both techniques.Methods[18 F]FDOPA PET imaging and microdialysis measurements were performed in unilaterally 6-hydroxydopamine-lesioned rats (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…This seems unlikely as dopaminergic signaling abnormalities were restricted to the striatum and not present in neocortex (Weinshenker et al, 2002b;Schank et al, 2006). Nevertheless, a NE replacement study, though experimentally challenging, would help rule out the possibility that dopamine is responsible for the effect we observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This seems unlikely as dopaminergic signaling abnormalities were restricted to the striatum and not present in neocortex (Weinshenker et al, 2002b;Schank et al, 2006). Nevertheless, a NE replacement study, though experimentally challenging, would help rule out the possibility that dopamine is responsible for the effect we observed.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this discrepancy is these studies' use of neurotoxins, particularly 6-hydroxydopamine (6-OHDA), to destroy noradrenergic neurons. 6-OHDA is somewhat nonspecific, as it kills dopaminergic (Uretsky and Iversen, 1970;Walker et al, 2013) as well as noradrenergic neurons, and acutely compromises cholinergic signaling (Bear and Singer, 1986). Further, depending on the route of administration and dosage, 6-OHDA lesions may not include all noradrenergic projections in the area of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the moderation of L-DOPA effects by WMC seems to follow a U-shape relation with no effect on MB control in low DA individuals and enhancement MB control in high baseline DA individuals. To our knowledge, only one animal study has directly investigated the relationship between L-DOPA metabolism measured with 18 F-DOPA PET and DA changes with L-DOPA and found that increases in DA metabolites elicited by L-DOPA is greater when DA synthesis capacity is higher [22]. Thus, individuals with higher DA synthesis capacity may produce more DA from L-DOPA, thereby enhancing MB control as observed previously in higher-WMC individuals [11].…”
Section: Introductionmentioning
confidence: 81%
“…6-OHDA-induced lesioning of dopamine neurons in rats is a widely used model of PD (Simola et al, 2007). Several studies demonstrated differences in IEG induction following administration of a D1like receptor agonist and the contents of dopamine and its metabolites between the lesioned and nonlesioned hemispheres in animals with unilateral 6-OHDA lesions, particularly in the striatum (Berke et al, 1998;Perese et al, 1989;Walker et al, 2013), and in the level of monoamine neurotransmitters in the substantia nigra, hippocampus and frontal cortex (Kamińska et al, 2017).…”
Section: Discussionmentioning
confidence: 99%